Formulasi Sediaan Gel Ekstrak Daun Alpukat (Persea americana Mill.) Sebagai Terapi Pengobatan Luka Bakar Terhadap Kelinci New Zeland White - Aprilia Rika Alvita; Tatiana Siska Wardani; Tiara Ajeng Listyani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Researched on burn wounds healing activity of extract of avocado leaft (Persea americana Mill.) in gel preparation forms were tested on rabbits New Zeland White. This study aimed to determine variations effect of concentration in gel extract of avocado leaft for the treatment of burn wounds in rabbits which had been wounded using hot metal. In this study, avocado leaft extract was obtained through maceration method and formulated into gel preparations with concentration of 1%, 2% and 5%. Gel base was used as a negativ control, namely carbomer 940 and Bioplacenton® gel was used as a positive control, applied to burns on the back of New Zeland White rabbits with a diameter of 1,5 cm. The avocado leaft extract gel activity test was carried out on 3 rabbit, each formulation was replicated 3 times and wound diameter measurements were taken on each day. Data on the percentage of burn wound healing was statistically analyzed using One Way ANOVA method. The result of the data analysis at a concentration of 5% obtained a sig value <0,05. Based on One Way ANOVA analysis of the five treatments, the most effective was avocado leaft extract gel with a concentration of 5%.